Visualization and flow velocity determination of molten polymers - Sterzyński, Tomasz; Bula, Karol (Polimery, 2021)
The determination of flow vectors of molten polymer by dies and mold cavities filling is a topic of many investigations, realized by various measurement techniques. The non-direct measurements are based on temperature or pressure fields determination along the flow channels, where the sensors are usually positioned in the streaming polymers, leading to flow field disturbance. The Laser Doppler Velocimetry (LDV) is an efficient touchless measurement technique of streaming gases and liquids velocity, delivering directly values of the flow velocity and its direction. Principle and examples of LDV determined flow velocity distribution, are presented. The direct flow lines determination maybe done by using markers with a plate-like form, scanning electron microscopy (SEM) observation of fractured product surface.